Green Purchase Decision on Mineral Waters' Environmental Packaging: Millennials Perspectives - Genoveva Genoveva; Rizky Aldi Rahdino (Program Studi Magister Manajemen FE Unsri, 2020)
Research purpose - This research aims to analyze the factors influencing green purchase decision of 100% recycled plastic material created by Aqua in Indonesia on millennials perspectives. Methods– The researchers used quantitative method with online questionnaire as the collection data tool. Sampling in this research is to use purposive sampling and collected 175 millennials respondents who live in Jabodetabek. The data analyze used SPSS ver.22 and Smart PLS 3.2.8. This research is trying to identify the result of 7 hypothesis that have been developed.Result - This research found out that green knowledge had no reliability to the other factors that were intended in the model. The model of variables of the research down from 4 to 3 which remaining green awareness, green purchase intention and green purchase decision to stay analyzed. The final result showed that there are significant factors influencing green purchase decision from environmental awareness, green purchase intention and from green awareness through green purchase intention. It is learned that the millennials who are aware to the environmental issues, will lead to the intention to buy green products.Originality / value– To authors best knowledge, this research is the first research about mineral water environment packaging that launching by Aqua on early of 2019 in Jabodetabek area. Moreover. millennials as green consumers are underrepresented in green purchase behavior literature.Keywords:Green Awareness, Green Knowledge, Green Product, Green Purchase Intention, Green Purchase Decision.